Pengaruh Gaya Kepemimpinan, Motivasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Kopi X Bekasi - Assyifa, Siti Nur; Dharmanto, Agus; Wijayanti, Murti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the influence of leadership style, motivation, and work environment on employee performance at Kopi X, Bekasi. The research uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to 32 respondents. The data were analyzed using multiple linear regression with SPSS 27 software. The results show that partially, leadership style and motivation do not significantly affect employee performance, while the work environment has a positive and significant effect. However, simultaneously, leadership style, motivation, and work environment have a positive and significant impact on employee performance. The implication of this study highlights the importance of a conducive work environment to improve performance, and the need to further evaluate leadership approaches and motivational systems.